(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
Deciding what product to buy, what goods to use, what provider to rely on are choices we are dealing with everyday. Neuroimaging can substantially contribute to the study of how we make these decisions and how we develop a form of attachment towards products and brands. Nonetheless, we cannot underestimate the problems connected to this approach. Beyond the technical and methodological limits, there are clear difficulties of interpretation. Indeed, starting from weak theories, it is difficult to gather meaningful data, even by using powerful technologies. Therefore, it is necessary to develop a neuroscientific approach, related to choices in buying and marketing, which is characterized by methodological rigor within the limits of a well defined sphere of concepts, in order to provide meaning to the charming path of the cognitive neurosciences.